In Vitro Screening for Antioxidant and Anticholinesterase Effects of Uvaria littoralis Blume.: A Nootropic Phytotherapeutic Remedy - Rahman, Abdur; Haque, Anamul; Sahab Uddin, Md.; Mohsin Mian, Md.; Abu Sufian, Mohammad; Mosiqur Rahman, Md.; Ali, Yusuf; Rajdoula Rafe, Md.; M. Abdel-Daim, Mohamed; Josim Uddin, Md.; Asaduzzaman, Md. (Journal of Intellectual Disability - Diagnosis and Treatment, 2017)
Background: Oxidative stress is strongly linked in the development of numerous chronic and degenerative disorders. Medicinal plants with antioxidant and anticholinesterase activities exert a key role for the management of oxidative stress related disorders mainly Alzheimer's disease (AD). Therefore the purpose of this study was to assess antioxidant potentiality and anticholinesterase inhibitory activity of crude methanolic extract (CME), petroleum ether fraction (PEF), chloroform fraction (CLF), ethyl acetate fraction (EAF) and aqueous fraction (AQF) of Uvaria littoralis (U. littoralis) leaves. Methods: The antioxidant compounds namely total flavonoids contents (TFCs) and total proanthocyanidins contents (TPACCs) were determined for quantities constituent’s characterization. Antioxidant capacity of U. littoralis leaves were estimated by the iron reducing power (IRPA), 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging and nitric oxide (NO) radical scavenging capacity. Anticholinesterase effects were estimated for acetylcholinesterase (AChE) and butyrylcholinestrase (BChE) activity. Results: The EAF of U. littoralis leaves showed the highest TFCs as compared to CLF, CME, PEF and AQF. TPACCs were also found highest in EAF. The highest absorbance for IRPA was found in EAF (2.220 nm) with respect to CME and other fractions at the highest concentration. The EAF showed best DPPH and NO radical scavenging activity with IC50 values of 31.63 and 55.47 μg/mL, respectively with regard to CME and remaining fractions. The PEF represents highest AChE inhibitory activity with IC50 values of 35.19 μg/mL and CLF showed highest BChE inhibitory activity with IC50 values of 32.49 μg/mL. Conclusions: The findings of the current study demonstrate the presence of antioxidant phytochemicals, likewise, turns out antioxidant and anticholinesterase potentiality of U. littoralis leaves which could be a prestigious candidate for the treatment of neurodegenerative diseases especially AD.